Effect of O2/Ar Gas Flow Ratios on Properties of Cathodic Vacuum Arc Deposited ZnO Thin Films on Polyethylene Terephthalate Substrate. (28th August 2016) - Huang, Chien-Wei; Yang, Ru-Yuan; Pan, Cheng-Tang; Weng, Min-Hang
Abstract : Cathodic vacuum arc deposition (CVAD) can obtain a good quality thin film with a low growth temperature and a high deposition rate, thus matching the requirement of film deposition on flexible electronics. This paper reported the room-temperature deposition of zinc oxide (ZnO) thin films deposited by CVAD on polyethylene terephthalate (PET) substrate. Microstructure, optical, and electrical measurements of the deposited ZnO thin films were investigated with various O2 /Ar gas flow ratios from 6 : 1 to 10 : 1. The films showed hexagonal wurtzite crystal structure. With increasing the O2 /Ar gas flow ratios, thec -axis (002) oriented intensity decreased. The crystal sizes were around 16.03 nm to 23.42 nm. The average transmittance values in the visible range of all deposited ZnO films were higher than 83% and the calculated band gaps from the absorption data were found to be around 3.1 to 3.2 eV. The resistivity had a minimum value in the 3.65 × 10 −3  Ω·cm under the O2 /Ar gas flow ratio of 8 : 1. The luminescence mechanisms of the deposited film were also investigated to understand the defect types of room-temperature grown ZnO films.